Nexus between regulatory sandbox and performance of digital banks: A study on UK digital banks - Patrick Bernard Washington; Shafiq Ur Rehman; Ernesto Lee (Journal of Risk and Financial Management, 2022)
It is debatable whether the regulatory Sandbox contributes to financial institutions' growth. We used a panel sample of 24 challenger banks from the UK. This study has reviewed digital banks' adoption of a regulatory sandbox to foster innovation in financial sectors. We assessed the regulatory tools that encourage FinTech innovations, focusing on the aims of financial stability. Therefore, we exploit the introduction of the Sandbox as a catalyst for digital banking and its heterogeneous effects on the financial performance of digital banks. Our research showed that regulatory sandboxes have a detrimental impact on the financial performance of digital banks, increasing compliance costs and efficiency costs. This study will contribute to the limited literature on regulatory Sandbox and its policy implication for the growth and performance of digital banks. The recommendation of this study would help to improve the regulation of the development of digital technologies in the UK.
Keywords: 650; financial performance; digital banks; sandbox; virtual banks